2018
DOI: 10.1515/humo-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqua aerobics on body composition, body mass, lipid profile, and blood count in middle-aged sedentary women

Abstract: Purpose. The aim of the present investigations was to determine the effects of aqua aerobics on body weight and composition, lipid profile, and selected blood count parameters in middle-aged sedentary females. Methods. Twenty-one women were randomly assigned to an experimental group (age 56.20 ± 2.57 years, height 162.80 ± 4.76 cm, weight 74.03 ± 3.84 kg) that participated in aqua aerobics classes three times a week for three months and a control group (mean age 56.44 ± 3.28 years, height 165.00 ± 3.91 cm, wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
(25 reference statements)
5
23
2
1
Order By: Relevance
“…The results of our study showed active elderly women had a higher quality of life than sedentary elderly women. The results of this study were consistent with the studies of Herman et al Bergamen et al and Ghaseminejad et al [6,21,40] , but werr in disagreement with the results of Fabrie et al [28] . Quality of life has a broad concept and includes dimensions of life.…”
Section: Acknowledgementsupporting
confidence: 70%
See 1 more Smart Citation
“…The results of our study showed active elderly women had a higher quality of life than sedentary elderly women. The results of this study were consistent with the studies of Herman et al Bergamen et al and Ghaseminejad et al [6,21,40] , but werr in disagreement with the results of Fabrie et al [28] . Quality of life has a broad concept and includes dimensions of life.…”
Section: Acknowledgementsupporting
confidence: 70%
“…Several age-related physiological problems that occur in the elderly will affect their quality of life. Given the specific requirements of the aging period, it is also essential to pay attention to quality of life in the elderly that is neglected in most cases [21] . Paying attention to quality of life and modification of lifestyle can greatly increase the efficiency and independence of the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…The hand search of the references of all relevant studies identified one relevant study (Arslan, 2011). After removal of duplicates and exclusion of studies based on predetermined criteria, the final sample included 9 RCTs (Araújo et al, 2015;Arslan, 2011;Jasiński et al, 2015;Kantyka, Herman, Roczniok, & Kuba, 2015;Kin-Isler & Kosar, 2006;Melam et al, 2016;Nagle et al, 2007;Novaes et al, 2014;Park et al, 2003) and 5 uncontrolled clinical trials (Duzova et al, 2018;Hallage et al, 2010;Pilch et al, 2017;Ruiz-Montero, Castillo-Rodriguez, Mikalacki, Nebojsa, & Korovljev, 2014;Said, Lamya, Olfa, & Hamda, 2017), the overview of which is shown in Table 2. The final sample included studies published primarily in Europe, Asia, North and South America.…”
Section: Resultsmentioning
confidence: 99%
“…Water aerobics and water fitness are kinds of aerobics that involve a long-period dynamic exercise with a medium intensity. The activity depends on the participant's age, health condition, and needs [8]. Water aerobics usually combine various techniques from aerobics including walking or running, going back and forth, jumping jacks, and some hand movements.…”
Section: Introductionmentioning
confidence: 99%
“…According to research done by Niu, water aerobics can reduce blood pressure on overweight and obesity female that has hypertension [1]. This activity is recommended for obesity patient, elderly or parents, and pregnant women [8]. This activity minimalizes a crash because it is done inside the water; making this sport usually urged for people who had an injury or susceptive of muscle injury [4], at least 90% of the bodyweight supported by the water, so the risk of getting a bone or muscle injury is very small.…”
Section: Introductionmentioning
confidence: 99%